2018
DOI: 10.5007/2175-7925.2018v31n4p15
|View full text |Cite
|
Sign up to set email alerts
|

Influência das águas do estuário do Rio Pará na fertilidade do solo das ilhas de várzea em Belém, Pará

Abstract: ResumoO Rio Pará é um imenso estuário formado por diversos rios e baías, compondo um grande contingente de água doce para o oceano. Nesse ambiente, encontram-se muitas ilhas, sendo 39 pertencentes à cidade de Belém. São ilhas com pouca porcentagem de área de terra irme, com presença de áreas cultivadas por agricultores familiares. O trabalho teve como objetivo avaliar o efeito da movimentação da água do estuário do Rio Pará na fertilidade do solo das ilhas de Belém, Pará. A amostragem foi realizada em 23 ilhas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Because of the heterogeneity and hydromorphism of floodplain soils, samples differed greatly in morphological, physical, chemical, and mineralogical characteristics, being grouped into different classes with different limitations and uses (Gomes et al, 2006;Lima et al, 2007). High levels of Al 3+ (1.12 cmol c dm −3 ) in soil limit plant development, as stated by Silva et al (2018). The value observed in the current study was much higher than those reported by Fajardo et al (2009) and Magalhães and Gomes (2013), namely 0.08 and 0.00 cmol c dm −3 , respectively, but within the range of 0.19 to 2.50 cmol c dm −3 described by Teixeira et al (2019) and Lima et al (2005) for several types of floodplain soils.…”
Section: Dispersion Of Normalized Data and Variable Weights Werementioning
confidence: 92%
See 2 more Smart Citations
“…Because of the heterogeneity and hydromorphism of floodplain soils, samples differed greatly in morphological, physical, chemical, and mineralogical characteristics, being grouped into different classes with different limitations and uses (Gomes et al, 2006;Lima et al, 2007). High levels of Al 3+ (1.12 cmol c dm −3 ) in soil limit plant development, as stated by Silva et al (2018). The value observed in the current study was much higher than those reported by Fajardo et al (2009) and Magalhães and Gomes (2013), namely 0.08 and 0.00 cmol c dm −3 , respectively, but within the range of 0.19 to 2.50 cmol c dm −3 described by Teixeira et al (2019) and Lima et al (2005) for several types of floodplain soils.…”
Section: Dispersion Of Normalized Data and Variable Weights Werementioning
confidence: 92%
“…The high variability of chemical and textural data is due to the fact that, although samples were collected on the banks of the Amazon River, collection points differed in vegetation and sediment discharges from tributaries and rivers that form the Amazon basin (Meade et al, 1979;Filizola and Guyot, 2011;Silva et al, 2005;Montanher et al, 2014;Silva et al, 2018).…”
Section: Quality Of Floodplain and Upland Soilsmentioning
confidence: 99%
See 1 more Smart Citation